2013
DOI: 10.1097/jom.0b013e3182794417
|View full text |Cite
|
Sign up to set email alerts
|

American Medical Association Impairment Ratings and Earnings Losses Due to Disability

Abstract: Impairment ratings are accurate predictors of disability severity on average, but their ability to measure disability could be improved with additional information on how the relationship between ratings and earnings loss varies according to patient and injury characteristics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 24 publications
0
7
0
Order By: Relevance
“…Comparing benefit levels to empirical estimates of earnings losses has become a standard approach to assessing the adequacy of workers' compensation benefits [Hunt, ; National Academy of Social Insurance, ]. Past studies from U.S. jurisdictions have often found that injured workers experience significant losses from work related injuries and that the replacement of lost earnings was low on average [Berkowitz and Burton, ; Biddle, ; Boden and Galizzi, 1999, 2003; Reville, ; Bhattacharya et al, ; Seabury et al, ]. However, prior studies have faced data limitations that could affect their assessments of benefit adequacy.…”
Section: Introductionmentioning
confidence: 99%
“…Comparing benefit levels to empirical estimates of earnings losses has become a standard approach to assessing the adequacy of workers' compensation benefits [Hunt, ; National Academy of Social Insurance, ]. Past studies from U.S. jurisdictions have often found that injured workers experience significant losses from work related injuries and that the replacement of lost earnings was low on average [Berkowitz and Burton, ; Biddle, ; Boden and Galizzi, 1999, 2003; Reville, ; Bhattacharya et al, ; Seabury et al, ]. However, prior studies have faced data limitations that could affect their assessments of benefit adequacy.…”
Section: Introductionmentioning
confidence: 99%
“…(1, 2) Studies focusing on the economic consequences of disabilities resulting from injuries in the workplace have found that workers lose up to 30 percent of their earnings even years after an injury. (35)…”
mentioning
confidence: 99%
“…The Functional Comorbidity Index was almost certainly underestimated, because diagnoses unrelated to the WC injury may not be reported to WC for billing purposes 38 . The WBI variable was essentially a lower bound estimate, 8 and the strength of association between impairment ratings and economic losses varies by jurisdiction and rating system 20,54‐57 . Although there is evidence that impairment ratings are associated with earnings losses, 56 there is also strong evidence that impairment ratings are inaccurate representations of work disability and at best explain a small amount of related earnings losses 54,55,57 .…”
Section: Discussionmentioning
confidence: 99%